You, me and something in between: The political subject of the inoperative community (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
The article explicits the question of the subject of a disobedient community as proposed by Jean-Luc Nancy. Without claiming a closed and univocal answer, it explores the possibilities for thinking a subject coherent with a community based on a relational ontology, emphasising the singular plural character of an "I" and a "we" that can respond to the demand of the "common".